Review on mucormycosis in the oro-facial region: an overview - Sonawane, Yogashree; Ahire, Ankeeta; Saha, Ananya (International Journal Of Community Medicine And Public Health, 2021)
The study aims to identify the clinical manifestation of mucormycosis in the oro-facial region to distinguish the role of meticulous intraoral examination for early and timely diagnosis based on the review of reported cases, to propose the role of diabetes mellitus as a predisposing risk factor for mucormycosis in the oro-facial region, to propose the association of traumatic incidents like tooth extraction as a risk factor for mucormycosis in immune-compromised individuals and to perceive the use of amphotericin-B in its treatment. A systematic review was conducted on an electronic database, Google Scholar to analyze the existing data for the clinical manifestation of mucormycosis in the orofacial region. Out of the existing literature on this topic for various timelines, a period of 10 years from 2011 to 2021 was selected for the study. The sample size was calculated taking into consideration the 99.99% confidence interval. The data was extracted from these relevant articles in Microsoft Excel, showing remarkable conclusions. Mucormycosis does not show stereotypical clinical manifestations and thus the diagnosis of mucormycosis has to be confirmed through culture studies and histopathological or radiological ways. Diabetes Mellitus serves as a predisposing factor for mucormycosis in the oro-facial region other than the COVID-19 infection and immune-compromised conditions. Amphotericin-B was a drug of choice for the treatment of mucormycosis by many practitioners. The only hindrance to its usage being its nephrotoxicity.